OPTIMAL MECHANISMS FOR INCOME TRANSFERS - Zeckhauser, Richard (American Economic Review, 1968)
The poor receive a sub-optimal amount of material goods through the natural economic processes of our society. Poor and non-poor alike seek to institute mechanisms that give something to the poor beyond what they get from the normal workings of the 'competitive' system. The fact that the non-poor share in this desire indicates that an externality is generated when the economic welfare of the poor is improved. On a collective basis, the non-poor are willing to pay for this externality. They sacrifice some of their income in support of redistributive programs that benefit the poor. In this paper we will not be concerned with moral or ethical values. We develop our analysis with the aid of a simple two-party model. One party is the representative poor man, the other the representative citizen. The representative citizen asks himself the central question of this essay. How should assistance programs to the poor be structured so as to maximize the utility function of the representative citizen. (Author)